The Recommended Aerobic Gymnastics Has Better Effects on Improving Cognitive and Motoric Ability in Children - Irfannuddin; Yunita Fediani; Budi Santoso; Minerva Riani Kadir; Masayu Rita Dewi (HM Publisher, 2018)
Abstract Background Cognitive and motoric ability has important role in children’s development, whereas exercise has benefit effects on those abilities. Knowledge materials mostly have dominant role in primary school curriculum. Physical exercise lesson is only complementary lesson without a target to improve children’s cognitive ability. We conducted a study to give evidence that 3x/week structured exercise program has better effect compared to 1 x/week exercise on cognitive and motoric skill ability in children. Materials and methods Children aged 6-8 years old were divided into treatment (n=34) and control group (n=33). Treatment group were performing fun aerobic gymnastics guided by trained instructor, 45 minutes each, 3 times a week for 8 weeks with intensity target. Control group were also performing the same gymnastic activity for only once a week with no target. Cognitive and motoric ability were assessed before and after intervention. Results A recommended regular exercise has better effect on executive function, reaction speed, coordination, flexibility and agility, compared to control. There were no differences on memory and balance ability. Both groups have shown better result for all indicators after exercise. Exercise in both groups has positive effect on cognitive and motoric ability, but a recommended 3 x/week regular exercise has better effects compared to 1 x/week exercise. Conclusions School program should give more portions for exercise activity in their curriculum. Keywords: Gymnastics exercise, cognitive ability, motoric ability